Light, Energy and the Environment 2014
DOI: 10.1364/pv.2014.ptu2c.2
|View full text |Cite
|
Sign up to set email alerts
|

Black silicon photovoltaics

Abstract: 35 words): An overview and comparison of different fabrication methods of black silicon is presented. Guidelines to optimize relevant parameters such as spatial frequencies and surface defect densities for optoelectronic applications such as photovoltaics will be given. Summary:The potential of silicon surfaces structured in the micro-and nanometer regime are widely known, e.g. in photovoltaic (PV) crystalline silicon (c-Si) solar cells [1][2], watersplitting by photo-electrochemical-catalysis (PEC) [3], phodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 13 publications
2
29
1
Order By: Relevance
“…For t RIE ≥5 min, R is very similar and lower than 2% in the full measurement range. The measured reflectance is slightly higher than what has been obtained previously using RIE texturing, where values down to less than 1% at normal incidence were obtained. We notice that the wafers used for this study are double‐side mirror‐polished, which have an initial higher R than saw‐damaged removed, solar‐grade wafers.…”
contrasting
confidence: 76%
See 1 more Smart Citation
“…For t RIE ≥5 min, R is very similar and lower than 2% in the full measurement range. The measured reflectance is slightly higher than what has been obtained previously using RIE texturing, where values down to less than 1% at normal incidence were obtained. We notice that the wafers used for this study are double‐side mirror‐polished, which have an initial higher R than saw‐damaged removed, solar‐grade wafers.…”
contrasting
confidence: 76%
“…Extracting S textured from the stabilized lifetime data results in values close to S planar (10.6 cm s −1 ) only for t RIE of 1.5 and 2 min (12.9 and 13.6 cm s −1 , respectively). We note that texturing with ICP for 3 min or shorter times in our equipment results in S textured values (before degradation) on par with or even better than the state‐of‐the‐art for p‐type CZ (11 cm s −1 in the review by Otto et al, 20 cm s −1 in the record b‐Si cells by Savin et al and 10 cm s −1 reported by Allen et al). This indicates potential for further efficiency improvements of b‐Si solar cells made by RIE texturing, if CCP is omitted from the texturing process.…”
mentioning
confidence: 46%
“…3 Black silicon surfaces can be achieved using different techniques that can be easily incorporated in the PV industry such as metalassisted wet-chemical etching (MACE), dry reactive ion etching (RIE), inductive couple plasma-reactive ion etching (ICP-RIE), laser structuring, and electrochemical etching. 4 Additionally, collateral benefits of b-Si have arisen recently improving low-cost substrates by removing saw surface damage in diamond-wire-sawn (DWS) wafers 5 or increasing the gettering effect during doping diffusion on Czochralski (CZ) c-Si solar cells. 6 All these advantages make black silicon etching a very attractive candidate to replace conventional acidic and alkaline texturizing approaches in the PV fabrication chain.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, commercial photodetectors (PDs) are mainly made from the inorganic semiconductor materials, including Si, ZnO, GaN, and InGaAs . These devices show fast response and high responsivity due to their outstanding electrical and optical properties.…”
Section: Introductionmentioning
confidence: 99%